On binary opposition and binarism : a long-distance dialogue between decolonial critique and the Lotmanian semiotics - Gherlone, Laura (2023)
Fil: Gherlone, Laura. Pontificia Universidad Católica Argentina. Facultad de Filosofía y Letras. Centro de Estudios de Literatura Comparada M. T. Maiorana; Argentina